Fluid Resuscitation for Refractory Hypotension - Valverde, Alexander (Frontiers in Veterinary Science, 2021)
Hypotension is a common occurrence, especially in anesthetized patients and in critical patients suffering from hypovolemia due to shock and sepsis. Hypotension can also occur in normovolemic animals, anesthetized or conscious, under conditions of vasodilation or decreased cardiac function. The main consequence of hypotension is decreased organ perfusion and tissue injury/dysfunction. In the human literature there is no consensus on what is the threshold value for hypotension, and ranges from < 80 to < 100 mmHg for systolic blood pressure and from < 50 to < 70 mmHg for mean arterial blood pressure have been referenced for intraoperative hypotension. In veterinary medicine, similar values are referenced, despite marked differences in normal arterial blood pressure between species and with respect to humans. Therapeutic intervention involves fluid therapy to normalize volemia and use of sympathomimetics to enhance cardiac function and regulate peripheral vascular resistance. Despite these therapeutic measures, there is a subset of patients that are seemingly refractory and exhibit persistent hypotension. This review covers the physiological aspects that govern arterial blood pressure control and blood flow to tissues/organs, the pathophysiological mechanisms involved in hypotension and refractory hypotension, and therapeutic considerations and expectations that include proper interpretation of cardiovascular parameters, fluid recommendations and therapy rates, use of sympathomimetics and vasopressors, and newer approaches derived from the human literature.